Parlache, crisis social y medios de comunicación - Castañeda Naranjo, Luz Stella; Henao Salazar, José Ignacio (Íkala, Revista de Lenguaje y Cultura, 1998)
Mass media have been determinant in the spreading ofParlache. This social dialect created by youngsters from lower class neighborhoods in Medellin to express their reality, is characterized by marginalization, uprooting and new "values" that emerge from a social crisis, due to factors such as social decay, violence, drug dealing, drug abuse and unemployment.